PENINGKATAN KINERJA BISNIS UMKM BATIK SEMARANG DENGAN MENCIPTAKAN KEUNGGULAN BERSAING - Rahmi Yuliana; Eldes Willy Filatrovi (FEB Universitas Sultan Ageng Tirtayasa, 2019)
The number of micro, small and medium enterprises (SMEs) in 2017 was recorded at 45 million business units. The majority of our economic actors are small and medium enterprises. In addition, this sector also absorbs 79 million people from the 100 million Indonesian workforce. Therefore, there must be various efforts made to develop small businesses in Indonesia, so that this sector develops better. Semarang City and Semarang Regency are the lowest cities for the number of batik entrepreneurs, therefore batik from Semarang City and Semarang Regency is the focus of research. If Semarangan Batik UKM cannot maintain its existence and make improvements to deal with market behavior that is increasingly open in the future, Semarangan Batik will be left far behind other batik-producing districts.population is 150 Semarangan Batik UMKM players in Semarang City and Semarang Regency as many as 150. The results of testing the effect of information technology utilization on competitive advantage is information technology has a positive effect on competitive advantage, the use of information technology has a positive effect on business performance, innovation strategies have a positive effect on excellence competing, innovation strategies do not have a positive effect on business performance and competitive advantage has a positive effect on business performance